Methotrexate vs expectant management for treatment of tubal ectopic pregnancy: An individual participant data meta‐analysis - Sarah Annie Solangon; Madelon Van Wely; Norah Van Mello; Ben W. Mol; Jackie A. Ross; Davor Jurkovic (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Ectopic pregnancy is an important health condition which affects up to 1 in 100 women. Women who present with mild symptoms and low serum human chorionic gonadotrophin (hCG) are often treated with methotrexate (MTX), but expectant management with close monitoring is a feasible alternative. Studies comparing the two treatments have not shown a statistically significant difference in uneventful resolution of ectopic pregnancy, but these studies were too small to define whether certain subgroups could benefit more from either treatment. Material and methods We performed a systematic review and individual participant data meta‐analysis (IPD‐MA) of randomized controlled trials comparing systemic MTX and expectant management in women with tubal ectopic pregnancy and low hCG (<2000 IU/L). A one‐stage IPD‐MA was performed to assess overall treatment effects of MTX and expectant management to generate a pooled intervention effect. Subgroup analyses and exploratory multivariable analyses were undertaken according to baseline serum hCG and progesterone levels. Primary outcome was treatment success, defined as resolution of clinical symptoms and decline in level of serum hCG to <20 IU/L, or a negative urine pregnancy test by the initial intervention strategy, without any additional treatment. Secondary outcomes were need for blood transfusion, surgical intervention, additional MTX side‐effects and hCG resolution times. Trial registration number: PROSPERO: CRD42021214093. Results 1547 studies reviewed and 821 remained after duplicates removed. Five studies screened for eligibility and three IPD requested. Two randomized controlled trials supplied IPD, leading to 153 participants for analysis. Treatment success rate was 65/82 (79.3%) after MTX and 48/70 (68.6%) after expectant management (IPD risk ratio [RR] 1.16, 95% confidence interval [CI] 0.95–1.40). Surgical intervention rates were not significantly different: 8/82 (9.8%) vs 13/70 (18.6%) (RR 0.65, 95% CI 0.23–1.14). Mean time to success was 19.7 days (95% CI 17.4–22.3) after MTX and 21.2 days (95% CI 17.8–25.2) after expectant management (P = 0.25). MTX specific side‐effects were reported in 33 MTX compared to four in the expectant group. Conclusions Our IPD‐MA showed no statistically significant difference in treatment efficacy between MTX and expectant management in women with tubal ectopic pregnancy with low hCG. Initial expectant management could be the preferred strategy due to fewer side‐effects.